USE OF CONTINUOUS CELLULAR AUTOMATA FOR SIMULATION OF THERMAL CONDUCTIVITY IN SYSTEMS WITH FIRST ORDER PHASE TRANSITION - Zhikharevich, Vladimir; Shumуlyak, Liliya (International Journal of Computing, 2014)
This paper is devoted to the use of cellular automata model for the study of some underlying physical processes. The basic approach and general methodology for the development of cellular automata models are examined through the example of heat transfer processes. It is shown that these models can be an alternative to the use of classical differential equations. It is proven that the model as a system of cellular automata is a good tool for the study of nonlinear problems of heat transfer and can describe a very complex behaviour of a system, despite the simplicity of its description.